Application of Hypertension Gymnastics to Reduce Blood Pressure in the Community in Health Center Facilities of South Banjarmasin - Okvitasari, Yenny; Seillawati, Seillawati; Agustin, Shalma; Saptadi, Irman; Safira, 'Ulya Noor; Salsabila, Salsabila; Asshiddiqie, M. Syauqi (UrbanGreen Central Media, 2025)
The increasing prevalence of hypertension, influenced by unhealthy lifestyles and lack of awareness, poses a serious public health issue. This project aims to introduce non-pharmacological holistic nursing interventions to support hypertension management within the community. The approach includes the application of warm foot soaking (hydrotherapy), foot massage, and hypertension exercises as simple and cost-effective therapies. A community-based health education and demonstration program was implemented to enhance public knowledge and encourage the independent practice of these interventions. The activity involved residents from Kelayan Timur who actively participated in the sessions. The results indicated improved understanding and willingness among participants to adopt the proposed therapies in daily life. This initiative demonstrated that non-pharmacological interventions can be well-received and practically applied in community settings, offering a valuable alternative in hypertension care. The conclusion highlights the effectiveness and sustainability of holistic methods as a supportive measure in managing hypertension, which can be disseminated through continued collaboration with healthcare institutions.